2019
DOI: 10.1002/ijc.32544
|View full text |Cite
|
Sign up to set email alerts
|

Use of nonaspirin nonsteroidal anti‐inflammatory drugs and risk of head and neck cancer: A nationwide case–control study

Abstract: Head and neck cancer (HNC) is the sixth most frequent malignancy with high mortality and substantial morbidity and hence there is a need for identification of preventive factors. Preclinical and observational studies have reported antineoplastic effects of nonaspirin nonsteroidal anti‐inflammatory drugs (NSAIDs), but studies of nonaspirin NSAID use and risk of HNC are sparse and with inconsistent results. We therefore conducted a register‐based case–control study nested in the entire Danish population. Cases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that the level of IL8 was associated with a worse overall survival in HNC patients [ 40 ]. Furthermore, a recent study found that consistent long-term use of non-steroidal anti-inflammatory drugs can be associated with a reduced risk of HNC [ 41 ]. One researcher found that anti-inflammatory drugs can reduce serum CRP [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the level of IL8 was associated with a worse overall survival in HNC patients [ 40 ]. Furthermore, a recent study found that consistent long-term use of non-steroidal anti-inflammatory drugs can be associated with a reduced risk of HNC [ 41 ]. One researcher found that anti-inflammatory drugs can reduce serum CRP [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a nested case–control study based on nationwide Danish registries using the personal identification number assigned to all Danish residents as key identifier. The study design has previously been described 6 . From the Danish Cancer Registry, 7 we identified all patients (cases) aged 30–84 years at diagnosis with histologically verified squamous cell HNC during 2000–2015, restricted to invasive squamous cell carcinoma (International Classification of Diseases‐O‐3 morphology codes: 8050–8084 and 8121–8123 with 3 as 5 th digit).…”
Section: Methodsmentioning
confidence: 99%